Current and future clinical utilities of Parkinson's disease and dementia biomarkers: can they help us conquer the disease?. (2nd November 2019) - Ho, Gilbert; Takamatsu, Yoshiki; Waragai, Masaaki; Wada, Ryoko; Sugama, Shuei; Takenouchi, Takato; Fujita, Masayo; Ali, Alysha; Hsieh, Mindy Hsin-I; Hashimoto, Makoto
ABSTRACT: Introduction : Biomarkers for Parkinson's disease and Alzheimer's disease are essential, not only for disease detection, but also provide insight into potential disease relationships leading to better detection and therapy. As metabolic disease is known to increase neurodegeneration risk, such mechanisms may reveal such novel targets for PD and AD. Moreover, metabolic disease, including insulin resistance, offer novel biomarker and therapeutic targets for neurodegeneration, including glucagon-like-peptide-1, dipeptidyl peptidase-4 and adiponectin. Areas covered : The authors reviewed PubMed-listed research articles, including ours, on a number of putative PD, AD and neurodegenerative disease targets of interest, focusing on the relevance of metabolic syndrome and insulin resistance mechanisms, especially type II diabetes, to PD and AD. We highlighted various issues surrounding the current state of knowledge and propose avenues for future development. Expert opinion : Biomarkers for PD and AD are indispensable for disease diagnosis, prognostication and tracking disease severity, especially for clinical therapy trials. Although no validated PD biomarkers exist, their potential utility has generated tremendous interest. Combining insulin-resistance biomarkers with other core biomarkers or using them to predict non-motor symptoms of PD may be clinically useful. Collectively, although still unclear, potential biomarkers and therapies can aid in shedding new light on novel aspects of both PD and AD.